Dyskeratosis congenita: a rare case report - Roy, Banasree; Mondal, Gobinda; Paul, Dilip Kumar; Kalam, Abul; Basu, Kausambi (Journal of Nepal Paediatric Society, 2013)
Dyskeratosis congenita is a rare congenital disorder affecting mainly the integumentary system. It is a progressive disease with involvement of bone marrow. A triad of hyperpigmentation, nail dystrophy and leucoplakia are characteristic of this disease. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8166 J. Nepal Paediatr. Soc. 2013;33(3):223-226